Elastyczne formy zatrudniania i organizowania czasu pracy jako sposób radzenia sobie z okresowymi zmianami w przedsiębiorstwie - Wrzosek, Krystyna (Elastic forms of employment and workforce hours organization as a way of handling periodical changes in an enterprise, 2006)
The paper presents some ways to elasticize enterprises that are affected by fluctuations in demand for workforce. Elastic forms of employment and their use for realization of changeable aims are discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 504-512